On the Possible Contribution of Natural Climatic Fluctuations to the Global Warming of the Last 135 Years - Ogurtsov, Maxim; Lindholm, Markus; Jalkanen, Risto (Scientific Research Publishing, 2017)
A number of numerical experiments with artificial random signals (the second order autoregressive processes), which have important statistical properties similar to that of the observed instrumental temperature (1850-2015), were carried out. The results show that in frame of the selected mathematical model the return period of climatic events, analogous to the current global warming (linear increase of temperature for 0.95˚C during the last 135 years) is 2849-5180 years (one event per 2849-5180 years). This means that global warming (GW) of the last 135 years can unlikely be fully explained by inherent oscillations of the climatic system. It was found however, that natural fluctuations of climate may appreciably contribute to the GW. The return period of climatic episodes with 0.5˚C warming during the 135 years (half of the observed GW) was less than 500 years. The result testifies that the role of external factors (emission of greenhouse gases, solar activity etc.) in the GW could be less than often presumed.
Keywords: natural oscillations; global warming; climate